Metabolic and Transcriptomic Profiling of Lilium Leaves Infected With Botrytis elliptica Reveals Different Stages of Plant Defense Mechanisms - Chai, Nan; Xu, Jie; Zuo, Rumeng; Sun, Zhengqiong; Cheng, Yulin; Sui, Shunzhao; Li, Mingyang; Liu, Daofeng (Frontiers in Plant Science, 2021)
Botrytis elliptica, the causal agent of gray mold disease, poses a major threat to commercial Lilium production, limiting its ornamental value and yield. The molecular and metabolic regulation mechanisms of Lilium's defense response to B. elliptica infection have not been completely elucidated. Here, we performed transcriptomic and metabolomic analyses of B. elliptica resistant Lilium oriental hybrid “Sorbonne” to understand the molecular basis of gray mold disease resistance in gray mold disease. A total of 115 differentially accumulated metabolites (DAMs) were detected by comparing the different temporal stages of pathogen infection. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed the differentially expressed genes (DEGs) and DAMs were enriched in the phenylpropanoid and flavonoid pathways at all stages of infection, demonstrating the prominence of these pathways in the defense response of “Sorbonne” to B. elliptica. Network analysis revealed high interconnectivity of the induced defense response. Furthermore, time-course analysis of the transcriptome and a weighted gene coexpression network analysis (WGCNA) led to the identification of a number of hub genes at different stages, revealing that jasmonic acid (JA), salicylic acid (SA), brassinolide (BR), and calcium ions (Ca2+) play a crucial role in the response of “Sorbonne” to fungal infection. Our work provides a comprehensive perspective on the defense response of Lilium to B. elliptica infection, along with a potential transcriptional regulatory network underlying the defense response, thereby offering gene candidates for resistance breeding and metabolic engineering of Lilium.